AN EXAMPLARY EMBODIMENT FOR A METHOD TO OBTAIN RAINFALL INFORMATION USING 48 SENSORS OF A RAINROSE INSTRUMENT - Sensus Wijonarko (Instrumentasi, 2018)
The purpose of this study was to show an application for a technique to gain rainfall information utilizing 48 sensors of a rainrose instrument. An analytic descriptive was employed as the study method. Even though the way to get the output was relatively complex, the result was not easy to be achieved using the available raingauges on the market.